KAEDAH TAKSIRAN ZAKAT PADI DAN KESANNYA TERHADAP PETANI: KAJIAN DI SELANGOR - Ab Rahman, Asmak (Jurnal Syariah, 2019)
This article analysed the impact of paddy zakah assessment to paddy farmers in Selangor. It concluded that the assessment which did not deduct paddy production cost and family expenses led to the misjudgement of the poor farmers by making them the zakah payers instead of zakah recipients.